Morbidity and mortality in premature or low birth weight patients with congenital heart disease in three European pediatric heart centers between 2016 and 2020 - De Silvestro, Alexandra; Reich, Bettina; Bless, Sarah; Sieker, Julika; Hollander, Willemijn; de Bijl-Marcus, Karen; Hagmann, Cornelia; Nijman, Joppe; Knirsch, Walter, the European Association Brain in Congenital Heart Disease; Bekker, Mirielle N.; Benders, Manon J. N. L.; et al. (Frontiers in Pediatrics, 2024)
Background The treatment of preterm and low birth weight (LBW) neonates born with congenital heart disease (CHD) requiring early cardiac intervention remains challenging. We aimed to analyze morbidity and mortality in this combined high-risk patient group. Methods A retrospective cohort study was conducted of preterm [<37 weeks gestational age (GA)] and/or LBW neonates (<2,500 g) born with a diagnosis of CHD, which requires invasive cardiac intervention (surgery or catheter) within their first year of life. Patients born between 2016 and 2020 and treated in three European pediatric heart centers were included. Results A total of 308 neonates (51% male) with CHD were included. Of those, 237 (77%) were born preterm, 259 (84%) were LBW, and 188 (61%) were both. The median GA was 35.4 weeks (interquartile range 33.3–36.9) and the mean birth weight was 2,016 ± 580 g. CHD was categorized as simple (12%), moderate (64%), or severe (24%). The overall complication rate was 45% and was highest in patients with severe CHD (p = 0.002). One-year mortality (19%) was associated with severe CHD, low relative birth weight in patients with genetic diagnoses, and low GA at birth, whereas GA at birth significantly impacted survival only after 3 months of life. Conclusions The high morbidity and mortality in preterm and LBW neonates with CHD reflect their complexity and consequent limited treatment feasibility.